PERAN KSPPS TAMZIS TERHADAP PENDAPATAN DAERAH KABUPATEN WONOSOBO MELALUI PRODUK PEMBIAYAAN MUDHARABAH (Studi Kasus KSPPS Tamzis Bina Utama Cabang Wonosobo) - Mila Fursiana Salma Musfiroh; Tiya Sugiyanti (LP3M Universitas Sains Al Qur'an, 2018)
The role of KSPPS Tamzis Bina Utama Wonosobo Branch onWonosobo district revenue through Mudharabah Financing,Discusses how mudharabah financing in KSPPS Tamzis, and howthe role of KSPPS Tamzis Bina Utama Main Branch Wonosoboregional income. Is a field research with qualitative approach. Datacollection through documentation and interviews. Data analysisusing descriptive analysis. Mudharabah financing provided byKSPPS Tamzis Bina Utama Wonosobo Branch to members of thewonosobo community from 2013 to 2017 reached approximately2,117 members. The revenue sharing from the financing ofMudharabah KSPPS Tamzis Wonosobo during the period 20152017 reached Rp. 7,929,109,000. of total mudharabah financingRp. 516.825. 964,374 distributed to members. Thus if mudharabahfinancing distributed by KSPPS Tamzis Wonosobo is increasing,and profits increase, it will increase the tax payments paid to thelocal government of Wonosobo regency. This is where the role ofKSPPS Tamzis Wonosobo through income from mudharabahfinancing, partly paid to the local government of Wonosobo districtas a form of obligation to pay taxes to the local government, thusthereby increasing the regional income of Wonosobo regency.